Effects of exogenous calcium additions on the ecological stoichiometric characteristics of various organs and soil nutrients and their internal stability in Pinus tabuliformis - Li, Hui; Zhao, Yaoyao; Weng, Xiaohang; Zhou, Yongbin; Huo, Yan; Zhang, Songzhu; Liu, Liying; Pei, Jiubo (Frontiers in Plant Science, 2024)
Pinus tabuliformis as a prominent species in silviculture within semi-arid regions, faced with the decline of plantations and other problems. Calcium plays an important role in alleviating drought stress and promoting nutrient absorption in plants. In order to explore the effects of exogenous calcium on nutrient uptake and ecological stoichiometry of Pinus tabuliformis, three-year seedlings were used as the test material for pot experiment. In this experiment, 5 exogenous calcium concentrations (0, 50, 100, 200, 400 mg·kg-1) were set. Through the determination of the nutrient contents of plants and soil, combined with the analysis of ecological stoichiometric characteristics and internal stability, the following conclusions were drawn. A trend wherein the contents of carbon, nitrogen, phosphorus, and potassium in different organs, as well as in the whole plant, exhibited an initial increase followed by a decrease with rising calcium concentrations, peaking at 50-100 mg·kg-1 calcium treatment. Concurrently, calcium concentrations in plant organs and the whole plant, along with effective soil calcium content, showed a gradual increase. The C:N, C:P, and N:P ratios in leaves showed "decreasing-increasing," "decreasing-increasing," and "increasing-decreasing" trends, respectively, with the gradual increase in added calcium concentration. Stems had "decreasing-increasing," "decreasing," and "decreasing" trends, while roots showed an "increasing-decreasing" pattern. Soil calcium correlated positively with total carbon (TC), total nitrogen (TN), total phosphorus (TP), total potassium (TK), and calcium content in leaves, stems, roots, and the whole plant at 0, 50, and 100 mg·kg-1 calcium concentrations. However, at 200 and 400 mg·kg-1 calcium concentrations, a positive correlation was observed between soil calcium and the calcium content of leaves, stems, roots, and the whole plant, while a negative correlation was noted between soil calcium and the content of TC, TN, TP, and TK. Upon the addition of different concentrations of exogenous calcium, most stoichiometric indices of various plant organs of Pinus tabuliformis seedlings demonstrated robust equilibrium. Soil exchangeable calcium and water-soluble calcium had significant effects on the stoichiometric characteristics of each organ. Notably, leaf and stem stoichiometric characteristics were affected by soil TN and available potassium (AK), with N:P ratios reaching a highly significant level.